The Impact of Covid on International Disputes - Lalani, Shaheeza; Shapiro, Steven G. (Brill, 2022)
With little warning, COVID-19 quickly escalated into a generational crisis, creating sustained havoc seen perhaps only in past cases of war, attack, and natural disasters. In the bedlam of the early months, health, science, political, and economic communities were hit with sudden force, required to quickly shift and rearrange the normal order of work. In arbitration, leaders took imperfect information to make dramatic decisions. In process and procedure, arbitral institutions, arbitrators, legal counsel, and clients were swept into this turmoil. In some cases, bold initiatives, still in design and testing, were quickly put into service, upsetting norms and traditions and the very notions of traditional process. The Impact of COVID on International Disputes includes contributions from legal practitioners and academics, takes a fresh look at issues addressed in international arbitration during the COVID-19 pandemic, gathering best practices, additional perspective and predictions based on current practices that will help parties, legal counsel and arbitrators in the future.